Sustaining Celuk Silver Craft Through Brand Image : Enhancing Competitiveness Based On Creative Tourism - Wisudawati, Ni Nyoman Sri; Sari, Putu Ratna Juwita; Gayatri , Ni Nyoman Putri; Bria, Anastasya Endria (Institut Pariwisata dan Bisnis Internasional, 2025)
Celuk silver crafts face competitive challenges in the creative tourism era, thus demanding increased innovation, strengthening digital branding, and developing creative tourism experiences. This study aims to analyze the influence of Product Innovation, Digital Branding, and Creative Tourism on Brand Image and Competitiveness using a quantitative approach based on SmartPLS 4.0. A total of 200 tourist respondents were involved in the measurement’s instruments demonstrated acceptable levels of validity and reliability. The inner model shows moderate to strong R-square values for brand image and competitiveness, while the outer model output indicates that all indicators are valid and reliable. The main results indicate that product innovation, digital branding, and creative tourism enhance brand image and competitiveness, with brand image serving as an important mediator. The findings, interpreted through the Resource-Based View (RBV) confirm that innovation, creative experiences, and digital branding capabilities are sources of sustainable competitiveness advantage for Celuk silver crafts.